Aimarjansī - Sālik, Ṣiddīq (al-Faiṣal Nāšrān, 2003)
Novel based on the problems of Locale, a village of Pakistan.
A novel Rāvalpinḍī : Maktabah-yi Sarmad, 1985. - In arab. Schrift, Urdu
Keywords: Urdu; Roman; Geschichte 1900-1980